The effect of music on recovery rate after a high intensity exercise - الذهلي عبدالله; محفوظة الكيتاني; رضوان حاج ساسي (Journal of Sport Science Technology and Physical Activities, 2025)
The purpose of this study was to determine the effects of music on specific psychological and physiological variables during recovery after high-intensity exercise. Study was conducted on a sample of (16) individuals with an average age (20.7 ± 0.6). Researchers used maximal aerobic rate maintenance testing for physical effects on study samples. Measurements included heart rate, lactate level, rate of perceived exertion, and feeling score. Measurements were taken before exercise, after exercise, and during the recovery period. Conclusion: listening to music during recovery had no effect on heart rate, lactate, or feeling score, but did affect perceived exertion.